FINITE AND NON-FINITE VERBS IN ENGLISH AND UZBEK LANGUAGES - Tuxtamisova Nurjanat Nurbayovna; Bafoyeva Nilufar Salimovna (PEDAGOGS, 2024)
Annotation: This article provides a comparative analysis of finite and non-finite verbs in English and Uzbek languages. It explores their functions, forms, and usage within sentences, highlighting similarities and differences between the two languages. While both languages distinguish between finite and non-finite verbs, English exhibits extensive verb inflection, whereas Uzbek relies more on suffixation and context. The article aims to aid learners in understanding the grammar and sentence structure of both languages effectively.